A comparison of the moral emotions concepts 'shame' and 'guilt' from the Western and Islamic perspectives - Sawai, Rezki Perdani; Mohd Noah, Sidek; Krauss, Steven Eric; Juhari, Rumaya; Abdullah, Salhah; Khalid, Muhammad Yusuf; Mohd Ghazali, Norzulaili (2015)
Shame and guilt are two higher-order emotions which are believed to play a role in motivating moral behavior and developing moral character. It is for this reason that they are also referred to as moral emotions. Emotions help people to distinguish moral features in specific contexts, to motivate moral behavior, and to undercut immoral behavior. The concept of moral emotions in the Islam and Western cultural traditions differs. The majority of Western psychologists consider shame as detrimental to psychological well-being. Guilt, however, is generally viewed as an adaptive emotion. In Islam, the moral character of a person is determined by how much shame (haya’) his heart possesses while guilt (nadam) motivates the person to ask for forgiveness from fellow beings and repentance to Allah SWT. The greater the shame and guilt of a person, the more they will stay away from sin, resulting in a better-mannered individual. Thus, the aim of this paper is to compare and contrast the concepts of shame and guilt from the Western and Islamic perspectives. The research is significant in contributing a deeper understanding of the role of emotions in human functioning.